К дезаграризированному селу? Сельское и аграрное население в свете выборочных данных Всеобщей переписи населения - Горлях, К.; Дронг, З.; Новак, П. (Социология: теория, методы, маркетинг, 2005)
Recent rural and agricultural changes in Poland have been analyzed in this paper. We
have particularly focused on the direction of these changes. We wondered whether
despite the particular historical development of the Polish agriculture, there is a
noticeable formation of the typical market-oriented farming and non-agricultural
economic activities among rural inhabitants. The answer to such a question has been
sought in the analysis of economic activity as well as changes in agrarian structure. The
National Census 2002 data show that agriculture is no longer the major source of
income for the significant part of the rural population. Moreover, the other large part
of this population derives the income from welfare and other kinds of benefits. At the
same time, the changes in the agrarian structure show the processes of diversification
of farms (the disappearing middle), concentration of land in larger farms, increasing
level of farm mechanization, increasing average size of landownership as well as the
declining number of them.